Adaptability in the Brazilian Capital Market: Aspects Associated with Efficiency Reported by Companies Listed in B3 - Paulo Vitor Souza de Souza; César Augusto Tibúrcio Silva (BBR: Brazilian Business Review)
This article aims to verify the influence of political uncertainty, accounting elements, and the macroeconomic environment on the (in)efficiency of securities traded by Brazilian public companies. Between 2000 and 2019, we used 275 non-financial companies with shares traded in B3. We performed regression tests with panel data for two samples, one balanced and one unbalanced, totaling two models. For each model, we performed an additional analysis using the Stepwise method. The dependent variable comprises the inefficiency of daily stock data. The independent variables comprise political-economic uncertainty, the companies' accounting indicators, gross domestic product per capita, and interest rate. We used controls related to the size, liquidity of the shares, and sectors of the companies. According to the selected sample, the results show that higher rentability companies tend to increase efficiency while liquidity positively or negatively affects efficiency. In periods where interest rates are high, there is less efficiency in predicting securities. These results aim to contribute to the literature on adaptive markets by providing evidence on defining aspects of Brazilian securities' efficiency variability.